Relationship between Utilization of Instructional Materials and Teachers’ Job Performance in Secondary Schools in North-West Zone, Nigeria - Shehu, Bello Gwandu; Asheik, Ali Kime; Liman, Tureta Abdulkadir (Kashere Journal of Education, 2025)
This study investigated the relationship between the utilisation of instructional materials and teachers' job performance in secondary schools in the North-West Zone, Nigeria. We raised three objectives, two research questions, and one hypothesis to guide the conduct of this study. The study adopted a correlational research design, and a sample of 370 teachers was drawn from a population of 24,821 secondary school teachers in the North-West Zone, Nigeria. Two instruments were used to collect data for this study: the Utilisation of Instructional Materials Questionnaire (UIMQ) and the Teachers' Job Performance Questionnaire (TJPQ). The instruments underwent content validation by a team of experts in the field of educational administration and planning and other experts in the Faculty of Education and Extension Services, Usmanu Danfodiyo University, Sokoto. The reliability of the instruments was assessed through a pilot test and a test-retest method conducted after an interval of three weeks, with the two sets correlated using the Pearson Product Moment Correlation Coefficient (PPMCC), yielding reliability indices of 0.78 for AIMC and 0.76 for TJPQ, respectively. Frequencies, percentages, means and standard deviations were used to answer the research questions, while PPMCC was used to test null hypotheses at the 0.05 level of significance. The findings of this study revealed that there was a positive and significant relationship between the use of instructional materials and teachers' job performance in secondary schools in the Northwest Zone, Nigeria. The study concluded that there was a low level of utilisation of instructional materials in secondary schools and a moderate level of teachers' job performance due to this low utilisation in the Northwest Zone, Nigeria. It was recommended that instructional materials should be utilised during teaching to enhance teachers' job performance and increase students’ academic performance.